2017
DOI: 10.1111/ans.14084
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lignocaine in colorectal surgery: a systematic review

Abstract: IVL has shown limited benefit towards reducing early pain and morphine consumption when compared with placebo in colorectal surgery. However, IVL did not show any significant reduction in pain or opioid consumption when compared with epidural. Further research investigating IVL combined with intraperitoneal local anaesthetic is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
3
11
0
1
Order By: Relevance
“…In the consumption of analgesics, our study showed that lidocaine was associated with lower opioid requirements in the first 24 hours after laparoscopic colorectal surgery, which was consistent with these studies . However, other studies showed that IV lidocaine could not reduce the consumption of opioids after other abdominal surgeries . The cause of this difference might be induced by the different type of surgery.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the consumption of analgesics, our study showed that lidocaine was associated with lower opioid requirements in the first 24 hours after laparoscopic colorectal surgery, which was consistent with these studies . However, other studies showed that IV lidocaine could not reduce the consumption of opioids after other abdominal surgeries . The cause of this difference might be induced by the different type of surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Lidocaine is a commonly used amide local anaesthetic with anti‐inflammatory and anti‐hyperalgesia effects. Previous meta‐analyses demonstrated that intravenous (IV) lidocaine could reduce postoperative pain and analgesia requirement, whereas the review of MacFater et al reported that IV lidocaine cannot effectively reduce early pain after colorectal surgery . Their findings were similar to the meta‐analysis that included 68 randomised controlled trials (RCTs), which showed that lidocaine had no advantage on enhancing gastrointestinal function recovery and reducing PONV and pain degree compared with placebo in various surgeries .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…IVL is another adjunct used for its effectiveness in the acceleration of return of bowel function following colorectal resection surgery, a finding corroborated by both this NMA and several meta‐analyses. However, it remains unclear whether IVL decreases pain and opioid consumption to a clinically significant degree.…”
Section: Discussionmentioning
confidence: 66%